Integrating Sad Kerthi local wisdom in the development of Tista Tourism Village toward sustainable tourism - Rosvita Flaviana Osin; I Made Bayu Wisnawa; I Wayan Agus Anggayana (Bahasa Indonesia, 2026)
Sustainable tourism development in Bali after being hit by floods requires an approach that integrates local wisdom to maintain a balance between economic development, cultural preservation, and environmental sustainability. This study discusses the integration of Sad Kerthi, a fundamental concept of Balinese local wisdom, in the development of Tista Tourism Village in Tabanan Regency as a model of sustainable tourism based on local culture. Through a qualitative approach with observation and interview methods with the Government, Village Head, and local communities, this study explores how Sad Kerthi principles are integrated in the planning and management of tourism villages. The results show that the integration of Sad Kerthi values has contributed significantly to environmental preservation, local community empowerment, and improving the quality of tourist experience. The application of Sad Kerthi is manifested in several aspects of tourism development, namely community participation in the decision-making process, preservation of cultural ceremonies and rituals, environmental conservation efforts, and a human-centered development approach. These findings indicate that the Sad Kerthi framework provides a sustainable model for tourism development in Balinese villages, which balances economic benefits with cultural integrity and environmental management.